THE SYMBOLISM OF NATURE IN SELECTED POEMS BY ROBERT FROST: A ROLAND BARTHES SEMIOTIC ANALYSIS - Nurjanah Azahra; Nurholis; R. Myrna Nur Sakinah (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2026)
This study examines the symbolism of nature in Robert Frost's The Sound of Trees and Stopping by Woods on a Snowy Evening using Roland Barthes' semiotic theory. The study aims to analyze how natural symbols construct meaning through the processes of denotation, connotation, and myth within Barthes' framework of first- and second-order signification. A qualitative descriptive method with a library research approach was employed. The primary data consist of the two selected poems, while secondary data were obtained from books, journal articles, and relevant literary criticism. The findings reveal that natural elements such as trees, woods, snow, and wind function not merely as descriptions of the physical environment but as symbolic signs that communicate broader cultural and ideological meanings. At the connotative level, these symbols represent ideas of freedom, contemplation, responsibility, personal transformation, and emotional reflection. At the mythological level, the symbols engage with cultural beliefs concerning mobility, self-determination, solitude, purity, and responsibility. However, rather than simply reproducing these cultural myths, Frost's poems also complicate and negotiate them by presenting the tension between personal aspiration and social obligation. The study demonstrates that Barthes' concept of myth provides a useful framework for explaining how ordinary natural imagery operates as a second-order sign system through which cultural values are constructed and critically examined in Frost's poetry.